NILAI LUHUR PRANATA MANGSA DALAM SISTEM PERTANIAN MODERN - Hyankasu Adeca Pandyambika Fatista Sitaningtyas (Universitas Islam Kadiri, 2016)
Pranata Mangsa is a dating system of Javanese farmers, and in each there is the hallmark of prey in nature, which can be used to signal to the activities in the process of planting for farmers. Local knowledge is derived from observations of the farmers over the past decades to find a that can be used as a handle in running the farming process. The grip is tangible knowledge about the state and the season is necessary for each person engaged in agriculture to reduce the failure rate. Events changing times cause a shift in climate, this led to the change of seasons also change the pattern. Institutions prey is divided into 12 months, with each month have the criteria and characteristics of each. The criteria and characteristics is used as a marker of the start of the growing season. Besides being used as a marker of the start of the growing season, institutions prey is also a doctrine of hope. Pranata prey system makes water as the most important points that must be considered. Increased utilization of water resources is not only caused by the high demand due to the high population growth but also by the various types of utilization of water resources. Water distribution and maintenance of irrigation systems (reservoirs) can use the reference of Pranata Mangsa. In the early months (gauze prey to prey Kapat) reservoir water sharing arrangements should be more careful, because the prolonged drought and lack of rainfall.